Chinese Breast Milk Fat Composition and Its Associated Dietary Factors: A Pilot Study on Lactating Mothers in Beijing - Wu, Wei; Balter, Adi; Vodsky, Victoria; Odetallh, Yatreb; Ben-Dror, Gai; Zhang, Yumei; Zhao, Ai (Frontiers in Nutrition, 2021)
Regional differences were found in breast milk composition. This study intended to profile composition of fatty acid (FA) and triacylglycerol (TAG) in Chinese breast milk, and to explore its association with maternal diet. Breast milk samples and data of 52 lactating women at 60-90 days postpartum were collected. FA composition was measured using GC-FID, and the TAG profile was detected by ultra-performance liquid chromatography system, coupled with accurate-mass quadrupole time-of-flight mass spectrometer. A semi-quantitative food intake frequency questionnaire and a one-time 24-hour dietary recall were used to evaluate the previous-month and short-term dietary intake, including dietary patterns, food groups and nutrients. Oleic-Palmitic-Linoleic (OPL) is the most predominant TAG within the Chinese human milk, followed by Oleic-Palmitic-Oleic (OPO), with an average ratio of OPL to OPO being 1.35. Linoleic acid (LA) and oleic acid (OA) accounted for 23.9% and 32.0% of total FAs, respectively. Among food groups consumed during the preceding month, LA content was positively associated with consumption of soybeans and soybean products (r=0.311, p=0.030), whereas a negative correlation was identified with seafood consumption (r=-0.302, p=0.030). Negative correlations were found between OA content and the consumption of soybeans and soybean products (r=-0.363, p=0.009), livestock and poultry meat (r=-0.375, p=0.006), nuts (r=-0.305, p=0.028) as well as cooking oil (r=-0.445, p=0.001). No significant associations were identified between LA and OA content and dietary patterns. This study confirmed a high OPL level in Chinese breast milk and revealed associations of FAs with maternal dietary intake.